2001
DOI: 10.1159/000052818
|View full text |Cite
|
Sign up to set email alerts
|

Increased Bone Volume and Bone Mineral Content in Xylitol-Fed Aged Rats

Abstract: Background: Our previous studies have shown that dietary xylitol supplementation protects against the loss of bone mineral after ovariectomy. The ovariectomy-induced decrease in trabecular bone volume is significantly retarded by dietary xylitol. Objective: To study whether dietary xylitol can protect against bone loss also during aging, a long-term experimental study was performed with rats. Methods: Twenty-four male Sprague-Dawley rats were divided into two groups. The rats in the control group were fed a ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…However, we demonstrated that xylitol enhances antibiotic elution from PMMA to a greater extent than does glycine (13,14), and xylitol itself has been shown to have antibacterial properties and to prevent biofilm formation (2,8,9,17,20). In a rat model, xylitol was also found to have a positive impact on bone density (11,18).…”
mentioning
confidence: 80%
“…However, we demonstrated that xylitol enhances antibiotic elution from PMMA to a greater extent than does glycine (13,14), and xylitol itself has been shown to have antibacterial properties and to prevent biofilm formation (2,8,9,17,20). In a rat model, xylitol was also found to have a positive impact on bone density (11,18).…”
mentioning
confidence: 80%
“…High glucose, sucrose and fructose generally result in lower BMD, particularly in magnesium deficiency, probably through reduced calcium absorption 47 . Lactose again appears to be beneficial for bone 48 , while xylitol can slow bone resorption, increasing BMD, BMC and biomechanical properties 49 . Mannitol and prebiotics can improve bone mineral absorption by increasing gut fermentation, resulting in greater mineral uptake in bone and improved BMD and bone strength 50 .…”
Section: Introductionmentioning
confidence: 99%
“…Xylitol mitigates the formation of dental plaque owing to its non-fermentability by plaque forming bacteria [11][12][13][14]. It is commonly used as a sugar substitute for diabetic patients because it is low in calories and its metabolism is not regulated by insulin.…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly used as a sugar substitute for diabetic patients because it is low in calories and its metabolism is not regulated by insulin. It was suggested as a therapeutic agent for glucose 6 phosphate dehydrogenase deficiency [11][12][13][15][16][17][18]. Xylitol is also known to improve health and biomechanical properties of the bone [12,13].…”
Section: Introductionmentioning
confidence: 99%